ANALYSIS ON POLYTECHNIC OF TONGGAK EQUATOR STUDENTS’ ERROR IN WRITING - Magpika Handayani (Jurnal Pendidikan Bahasa, 2018)
Students are required to express something in the form of written expression because it is one of skill in learning a language. Students are required to be good at grammar to regulate every word with a good structure. However, there is an error made by students that are caused by some grammatical factors such as punctuation, word selection, tenses, spelling, use of article and capitalization. This research is qualitative research, and the writer describes the error made by students by looking at the factors commonly cause the error. The results showed that student error in writing lies in misused form, words form, words choice, verb tense, misplace words, spelling, punctuation, capitalization, and article. The occurrence of an error in writing is due to first language interference, style of translation, and carefulness in writing. The dominant error made by the student lies in the use of the word form in the sentence.Keywords: analysis, writing error, grammatical errors.